2021
DOI: 10.1155/2021/2860007
|View full text |Cite
|
Sign up to set email alerts
|

Angle-Resolved Intensity of In-Axis/Off-Axis Polarized Micro-Raman Spectroscopy for Monocrystalline Silicon

Abstract: Monocrystalline silicon (c-Si) is still an important material related to microelectronics/optoelectronics. The nondestructive measurement of the c-Si material and its microstructure is commonly required in scientific research and industrial applications, for which Raman spectroscopy is an indispensable method. However, Raman measurements based on the specific fixed Raman geometry/polarization configuration are limited for the quantified analysis of c-Si performance, which makes it difficult to meet the high-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, their stress states are uniaxial or biaxial in fact [26][27][28][29], which is not relevant to the decoupling analysis of complex stress states (regardless of what they claim [30]). Furthermore, for complex silicon samples such as polysilicon and textured silicon [27,31], experiments have shown that a large NA (NA > 0.4) indeed provides more abundant experimental information than a small NA (NA ≤ 0.4) [28,30,32]. However, there has been a lack of a theoretical and experimental basis for the problem of decoupling the analysis of complex stress states with large-NA objective lenses, such as {100} c-Si.…”
Section: Introductionmentioning
confidence: 99%
“…However, their stress states are uniaxial or biaxial in fact [26][27][28][29], which is not relevant to the decoupling analysis of complex stress states (regardless of what they claim [30]). Furthermore, for complex silicon samples such as polysilicon and textured silicon [27,31], experiments have shown that a large NA (NA > 0.4) indeed provides more abundant experimental information than a small NA (NA ≤ 0.4) [28,30,32]. However, there has been a lack of a theoretical and experimental basis for the problem of decoupling the analysis of complex stress states with large-NA objective lenses, such as {100} c-Si.…”
Section: Introductionmentioning
confidence: 99%